Norse burial practices and medieval fear of revenants in the myth of Ragnarök. - Tozzi, Arturo (Neohelicon, 2024)
After the introduction of the Christian religion, a traumatic shift took place in the Norse approach to death rituals. Transition went with strains between the ancient era of cremation and the new inhumation period. We argue that the myth of Ragnarök, written after Icelandic Christianization, might refer to the Norse mythical past of funeral pyres as opposed to the Christian funeral practices. We provide novel insights about the role of Odin, who is swallowed by Fenrir as if he has been buried in the ground, and of Surtr, who burns the world to restore the purifying role of the flames. Yet, the fear among Norse people for dead revenants can be traced in the Ragnarök myth, in which malevolent and benevolent characters return from death. Ragnarök sets out how to cope with revenants either to keep them quiet, or counteract their evil powers, or fully remove their menace. Concerns about revenants were more compelling for Medieval Norsemen after Christianization, when the corpses could not be any longer destroyed/purified by the fire, but rather had to lie in the earth with easy access to return from death. Summarizing, we argue that: (a) Ragnarök outlines the transition from Norse to Christian burial practices and the ways Norsemen coped with this trauma; (b) Ragnarök is also a history of revenants, in which Norsemen strive to deal with the uncanny powers of dead.